Contribution of women in fisheries and fishery related activities in ponnalai, jaffna, sri lanka - Nilakshana, K.; Shobiya, P.; Dilini, J.G.B.D.; Ragavan, N.; Sivashanthini, K.; Sutharshiny, S. (University of Jaffna, 2021)
Women’s involvement in fisheries seems to be largely invisible and unacknowledged in Jaffna Peninsula. Thus, the present study was conducted in Ponnalai village to determine the active participation of women in fisheries, analyse their socio economic status and suggest appropriate measures to improve their livelihood. Data were collected using a structured questionnaire and through interviews from October to December 2018. Randomly selected, 25 women fisher folks were interviewed and collected data were subjected to descriptive statistical analysis. In the study area, women were primarily involved in hand picking of shrimps and crabs. Results revealed that 100 % of responders were Hindus and were from traditional fishing families. It was found that 72 % of women were above 50 years in age. The educational status of fishers showed that 80% were illiterate. The fisheries sector is characterized with the participation of married and widowed women (64 %). Number of children per women fisher folk was 7 - 9 (52 %). The average monthly fish production varied between 130 kg to 312 kg (60 %) and monthly income varied from Rs.7, 800 to Rs.13, 000. It was apparent that the socio-economic status of women fishers in the study area was poor. Lack of government support, poor literacy rate and low income were the major identified constraints faced by the women fisher folk of this village. Therefore, support from governmental or non-governmental organizations by providing subsidies, loans and technological assistance are essential to improve the livelihood and their socio-economic status.
Keywords: Fisher women; Hand fishing; Livelihood; Shrimp; Socio - economics